(untitled) (Scientific journal of the Fergana State University, 2023)
The purpose of the research was to determine the effectiveness of the use of mineral supplements in the diet of bulls during cultivation. The experiments were carried out on 30 heads of bulls, selected according to the principle of analogues. The diets of the calves of the experimental group, unlike the control group, were balanced according to the detailed norms for the content of calcium, phosphorus, cobalt, copper and iodine by introducing fluorine-free phosphate and salts of the corresponding microelements. The results of the studies showed that in the same intake of minerals in the diets of all bulls (about 59 g per 1 kg of dry matter), the digestibility and use of nutrients and energy in the bulls of the experimental group were at a higher level than in the bulls of the control group. Thus, the digestibility of dry and organic matter, energy and protein increased by 1.8-3.2%, and the digestibility of fiber - by 9.7%.